Wear Behavior of an Unstable Knee: Stabilization via Implant Design?. (9th September 2014) - Reinders, Jörn; Sonntag, Robert; Kretzer, Jan Philippe
Abstract : Background . Wear-related failures and instabilities are frequent failure mechanisms of total knee replacements. High-conforming designs may provide additional stability for the joint. This study analyzes the effects of a ligamentous insufficiency on the stability and the wear behavior of a high-conforming knee design. Methods . Two simulator wear tests were performed on a high-conforming total knee replacement design. In the first, a ligamentous-stable knee replacement with a sacrificed anterior cruciate ligament was simulated. In the second, a ligamentous-unstable knee with additionally insufficient posterior cruciate ligament and medial collateral ligament was simulated. Wear was determined gravimetrically and wear particles were analyzed. Implant kinematics was recorded during simulation. Results . Significantly higher wear rates (P ≤ 0.001 ) were observed for the unstable knee (14.58 ± 0.56  mg/10 6 cycles) compared to the stable knee (7.97   ±   0.87  mg/10 6 cycles). A higher number of wear particles with only small differences in wear particle characteristics were observed. Under unstable knee conditions, kinematics increased significantly for translations and rotations (P ≤ 0.01 ). This increase was mainly attributed to higher tibial posterior translation and internal rotations. Conclusion . Higher kinematics under unstable test conditions is a result of insufficient stabilization via implant design. Due to the higher kinematics, increased wear was observed in this study.